BeGuideWell: A prospective cross-sectional study analysing the awareness and opinions of nursing students in Poland on the usefulness of European Society of Cardiology guidelines in post-graduate education programme. (October 2019) - Uchmanowicz, Izabella; Wleklik, Marta; Hill, Loreena; Lisiak, Magdalena; Chudiak, Anna; Lomper, Katarzyna; Lambrinou, Ekaterini; Jennings, Catriona; Fitzsimons, Donna
Background: The role of clinical guidelines is to provide patients with the best quality, evidence-based care. Nurses are actively involved in the development of the European Society of Cardiology guidelines. A number of the guidelines include specific recommendations relating to nursing duties and, hence, nurses require necessary knowledge and skills for their implementation. Inclusion of the guidelines in the curricula for university nursing programmes could facilitate their implementation to everyday practice. Aim: The purpose of this study was to determine the awareness and opinions of Polish nursing students who participated in a guideline-based Master of Science education programme about the usefulness of the European Society of Cardiology guidelines. Methods: A prospective and cross-sectional research design was used and Strengthening the Reporting of Observational studies in Epidemiology guidelines were followed. A total of 188 nursing students (mean age 31.18±10.41 years) who met the inclusion criteria were invited to complete the BeGuideWell survey. This instrument included 16 questions: five on participants' demographics and 11 addressing the issues associated with the European Society of Cardiology guidelines. The Yates chi-squared test or Fisher exact test were used for statistical analysis. Results: The majority of students had become familiar with the diagnostics and treatment of acute and chronic heart failure. Nearly half of the students documented that they had never heard of the European Society of Cardiology guidelines before starting the Master of Science programme. Most students found the European Society of Cardiology guidelines helpful for their university education. Most respondents stated that the guidelines were useful in their everyday practice and believed that they contributed to better quality of patient care. Conclusions: Students can become more familiar with the European Society of Cardiology guidelines during the course of their post-graduate education, preparing them to implement the European Society of Cardiology guidelines in their everyday practice.